DOES AUTHENTIC ASSESSMENT PROMOTE CRITICAL THINKING? EXPERIENCE OF TWO EFL TEACHERS IN INDONESIA - Umam, Amalul; Riana Rahmawanti, Movi; Jaelani, Alan; Lisdawati, Lilis (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2024)
This study investigated the impact of authentic assessment on students' critical thinking in English classes. The study targeted two English teachers who had experience using authentic assessment in their classrooms. Data was collected through observation, in-depth interviews, focus group discussions, and documentation. The findings of the study showed that authentic assessment had a positive impact on students' critical thinking. Students who participated in authentic assessments were more motivated to learn, were better able to apply their English skills in a real-world context and were more likely to engage in critical thinking. The study also identified several opportunities/dispositions that promoted students' critical thinking in authentic assessments. These included teamwork and monitoring, which helped students identify other people's ideas, evaluate the evidence for a particular issue, reflect on an issue by bringing in logical opinions, draw conclusions about an issue, and present their points of view. The findings of this study suggest that authentic assessment is a valuable tool for promoting critical thinking in English classes. Authentic assessments can help students develop the skills and knowledge they need to succeed in college and the workplace.